Digital Infrastructure Investments and Tourism Development in Cameroon: Evidence from an ARDL Approach - Gérard, Tchouassi; Domtchouang Guylène Audrey, Nguétchouo (Eco-Tourism and Sustainable Development, 2025)
The development of digitalization, particularly through information systems, has led to a profound transformation of the tourism industry both in terms of operational practices and structural organization making digital infrastructure a key partner in the sector. This transformation has encouraged economic stakeholders to invest in digital infrastructure to enhance connectivity and improve access to digital services. The objective of this research is to assess the impact of digital infrastructure investment on tourism development in Cameroon. To achieve this, we applied the ARDL model using data over a 22-year period, from 2000 to 2021. Tourism development was measured through international tourist arrivals, while digital infrastructure investment was captured via private investment in digital technologies. Our findings highlight that both private investment in digital infrastructure and foreign direct investment (FDI) are significant and positive determinants of international tourist arrivals in Cameroon. However, the results also reveal a contrasting effect over time: while private digital investment has a significantly negative impact on tourist arrivals in the short term, its long-term effect is both positive and statistically significant. This implies that increased private sector investment in digitalization enhances access to digital tools among tourism actors, enabling them to better promote Cameroon’s image both nationally and internationally, and to tailor their offerings to the preferences and needs of visitors.